CONCEPT OF TEMPORALITY IN UZBEK AND ENGLISH LITERARY WORKS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The concept of temporality occupies an important place in literary studies because time functions not only as a chronological dimension but also as an artistic and narrative category. In literary works, temporality organizes the sequence of events, shapes narrative perspective, and influences the reader’s perception of characters and themes. This article investigates the concept of temporality in Uzbek and English literary works from a comparative perspective. The research examines narrative strategies used to represent time, including chronological narration, flashbacks, cyclical time structures, and psychological temporality. Examples from Uzbek and English prose are analyzed in order to reveal similarities and differences in the representation of time in the two literary traditions. The study shows that while both traditions employ various temporal techniques, Uzbek literature tends to emphasize historical continuity and cultural memory, whereas English literature often highlights subjective and experimental representations of time.